Evaluasi Pertumbuhan Beban Listrik Di Kota Manokwari Menggunakan Metode Trend: Evaluation Of Electricity Load Growth In Manokwari City Using Trend Method - Charles Teurupun; Henny A B Lesnussa; Abdul Z Patiran (Universitas Papua, 2023)
Manokwari city is the capital of Papua Barat which is developing, along with the development and increase in the number of residents in this city so that, demand for electrical energy in this city is increasing. Factors that affect the level of electrical energy demand in the city of Manokwari are population growth, increase in the number of electricity customers, number of industries, and economic factors, namely Gross Regional Domestic Product (GDP). The method used in this study is the trend analysis method, which is used to see the linearity of increasing factors that affect the growth of electricity loads in the city of Manokwari. The Growth each of these factors will be a reference for future researchers to forecast the growth of electricity load in the city of Manokwari. From the results obtained, the value of R-square or R² aims to determine how big the model is. The higher of R² value, the better the prediction model from the results of the research conducted, the R² value of the customer growth trend of 99% affects the growth trend, the R² of the population growth trend of 93%, the R² of the power trend generated by 97% and the R² value of the GDP trend of 56%. Manokwari City